2010
DOI: 10.1002/0471142956.cy0933s52
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Endothelial Cells and Progenitor Cell Subsets in Human Peripheral Blood

Abstract: An assay for circulating cell subsets in human peripheral blood by flow cytometry is used as a biomarker to determine cardiovascular disease risk and tumor responsiveness to chemotherapy since endothelial progenitor cells (EPCs) function in vasculogenesis and angiogenesis. Despite analytical advances in polychromatic flow cytometry (PFC), conventional approaches are routinely utilized to enumerate and isolate EPCs, which has led to varied results in clinical studies, potential cellular misidentification, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(134 citation statements)
references
References 28 publications
6
127
0
1
Order By: Relevance
“…Therefore, 138 patients were included in the study. for dead cells (15)(16)(17). Data acquisition was performed on a FACS Aria cytometer equipped with FACS Diva 5.0 software (BD) and analyzed by Flowjo software (Tree Star).…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 138 patients were included in the study. for dead cells (15)(16)(17). Data acquisition was performed on a FACS Aria cytometer equipped with FACS Diva 5.0 software (BD) and analyzed by Flowjo software (Tree Star).…”
Section: Trial Designmentioning
confidence: 99%
“…A minimum of 5,000, 000 events was acquired. The boundary between positive and negative cells was placed using fluorescence-minus-one controls and an internal control (16,17). Figure 1 illustrates the sequential gating strategy to mark EPCs for in-…”
Section: Trial Designmentioning
confidence: 99%
“…Timmermans et al concluded that true EPCs (EOCs) from human blood are CD34+CD45-CD133-VEGFR-2+ (both CD133 negative and CD45 negative), whereas CD34+CD45+CD133+VEGFR-2+ cells are early outgrowth EPCs of hematopoietic origin [25]. In a multi-color flow cytometry protocol for identifying EPC, Estes et al, distinguishes between early EPCs of hematopoietic lineage, which are CD45 positive, and true EPCs (referred to as "ECFCs"), which are CD45 negative [29].…”
Section: Traditional Classification Of Endothelial Progenitor Cellsmentioning
confidence: 99%
“…These cells may be recruited to denuded vessels in ischemic sites, but they do not directly become persistent vascular endothelial cells or display de novo in vivo vasculogenic potential. Rather, they display potent paracrine properties regulating new vessel formation via angiogenesis [73,74]. Yoder et al [33,64,75] refer to these cells as proangiogenic hematopoietic cells.…”
Section: Different Populations Of Endothelial Progenitor Cellsmentioning
confidence: 99%